Hydrogen sulfide improves vascular repair by promoting endothelial nitric oxide synthase-dependent mobilization of endothelial progenitor cells. Issue 5 (May 2019) - Hu, Qingsong; Ke, Xiao; Zhang, Tao; Chen, Yangxin; Huang, Qingsheng; Deng, Bingqing; Xie, Shuanglun; Wang, Jingfeng; Nie, Ruqiong
Abstract : Background: Endothelial progenitor cells (EPCs) play a crucial role in endothelial repair after arterial injury. Hydrogen sulfide (H2 S) is a novel gasotransmitter that regulates vascular homeostasis. Method: We investigated whether exogenous H2 S could facilitate EPCs in repairing arterial injury. Results: Sodium hydrosulfide (NaHS), a precursor of H2 S, promoted re-endothelialization and inhibited neointima formation in a rodent carotid artery injury model. Flow cytometric analysis revealed that NaHS treatment significantly increased the yield of EPCs after vascular injury. Furthermore, NaHS enhanced the capacity of EPCs to the luminal surface of injured arteries in wild-type mice, which had received a bone marrow transplantation from tie2-GFP donor mice. However, this enhancing effect was greatly attenuated in endothelial nitric oxide synthase knockout mice (eNOS −/− ). In-vitro incubation of human EPCs with NaHS not only increased the yield of EPCs, but also enhanced their adhesion and colony formation capacities. Treatment with an eNOS inhibitor (L-NAME) blocked the effects of NaHS on EPCs functions. Conclusion: H2 S enhances eNOS-dependent mobilization of bone marrow-derived EPCs and facilitates re-endothelialization following vascular injury. Abstract : Supplemental Digital Content is available in the text